(untitled) (Research, Society and Development, 2020)
Visitation impacts include any direct human action that causes damage to the natural environment, related to the visitor’s inappropriate behavior or planning problems for the use demand. Thus, the objective was to evaluate the possible impacts caused by the visitation of two main trails (Costão and Deserta), located in the Sustainable Development Reserve of Barra do Una, during the summer (high visitation period) and autumn (low visitation period) seasons of 2017. For this, Costão and Deserta trails were sectioned, with 4 and 10 points respectively, where physical, biological and social impacts indicators were evaluated using the Visitor Impact Management method. The findings demonstrated that, in both trails, a reduction in the impacts related to the drainage problems, when comparing the seasons of the summer with the autumn. The presence of garbage on the Deserta trail in the autumn season was smaller compared to summer, while damages to the natural resources on the Costão trail were higher in the autumn than in the summer. Although the trails studied are located in a Conservation Unit, the lack of public visitation control, as well as the lack of infrastructure collaborates in a negative way, resulting in damages of different severities. Finally, the actions proposed in the present study, such as guided trail with environmental monitor, control of public visitation, installation of handrails, steps and signboards can be beneficial to reduce and / or reverse the impacts found in both trails.